Coalitionally strategy-proof rules in allotment economies of homogeneous indivisible objects - Kentaro Hatsumi; Shigehiro Serizawa (Osaka University, Institute of Social and Economic Research (ISER), 2007)
We consider the allotment problems of homogeneous indivisible objects among agents with single-peaked and risk-averse von Neumann-Morgenstern expected utility functions. We establish that the rule satisfies coalitional strategy-proofness, same-sideness, and strong symmetry if and only if it is the uniform probabilistic rule. By constructing an example, we show that if same-sideness is replaced by respect for unanimity, the statement does not hold even with additional requirements of peaks-onlyness and continuity.
Keywords: C72; D71; D81; 330; coalitional strategy-proofness; homogeneous indivisible objects; single-peakedness; risk-averseness; uniform probabilistic rule; Soziale Wohlfahrtsfunktion; Entscheidung bei Unsicherheit; Erwartungsnutzen; Risikoaversion; Nichtkooperatives Spiel; Theorie